2004
DOI: 10.1128/aem.70.5.3005-3012.2004
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Single-Chain Antibody Expression in Quiescent Escherichia coli

Abstract: Quiescent Escherichia coli cells are generated by overexpressing the Rcd transcript in an hns-205 mutant host. The resulting nongrowing, metabolically active cells were used here to express a single-chain antibody fragment (scFv) in shake flask and fermentor cultures. The expression system is based on two plasmids; one carries the product gene expressed from P L under the control of the cI857 temperature-sensitive repressor, while the second expresses Rcd from P R . Shifting the culture from 30 to 42°C induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…Several reports have shown that the PelB signal peptide can successfully secrete scFvs into the periplasm or medium (31,38,39). However, in our study, use of a commercial expression vector with the PelB signal peptide after transformation with PelB-V L -V H or PelB-V H -V L resulted in no growth of either E. coli strain BL21(DE3) or Rosetta (DE3) on selection plates.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Several reports have shown that the PelB signal peptide can successfully secrete scFvs into the periplasm or medium (31,38,39). However, in our study, use of a commercial expression vector with the PelB signal peptide after transformation with PelB-V L -V H or PelB-V H -V L resulted in no growth of either E. coli strain BL21(DE3) or Rosetta (DE3) on selection plates.…”
Section: Discussioncontrasting
confidence: 45%
“…Consequently, two types of C4 scFvs that were 723 bp long with different orientations of the heavy and light chain variable regions (V L -V H and V H -V L ) were constructed ( Construction and expression of soluble C4 scFvs. scFvs frequently form inclusion bodies when they are overexpressed in bacterial cytoplasm (22,31,32). When pET-S tag vectors containing the C4 scFvs (Fig.…”
Section: Generation Of a Broad-spectrum Mab Against Potyviruses With mentioning
confidence: 99%
See 2 more Smart Citations
“…As a test of the synthetic capacity of Q-Cells, their ability to express a single-chain antibody fragment (scFv) in high-density shake flask and fermenter cultures was investigated [4]. The scFv gene was tagged with a pelB leader that resulted in the majority of product being secreted into the culture supernatant.…”
Section: Introductionmentioning
confidence: 99%